Piladora manual de Café como valor Ancestro-Cultural Chillano, basado en sus labores cotidianas, representado en la técnica del tallado en Madera - Ajila Celi, Jorge Paúl (2012)
Speaking of art as a representation of a people or culture, we take as a reference the sculpture and carving that is immersed in it since its inception, allowing asocial reality with the ancestor-cultural aspect of peoples.